Avulsion of the Femoral Attachment of the Medial Collateral Ligament of the Knee Associated to Complete Tear of the Posterior Cruciate Ligament: A Case Report - Haddad, Sleiman; Sallent, Andrea; Minguell, Joan; Castellet, Enric (The Surgery Journal, 2017)
Medial collateral ligament (MCL) of the knee is one of the most commonly injured ligaments of the knee. Incidence of posterior cruciate ligament (PCL) injuries can vary widely. Conservative treatment has shown good clinical outcomes and relatively rapid return to play in both injuries alone. We present the case of a 38-year-old male who presented a combined MCL avulsion injury and PCL tear treated surgically. The PCL was reconstructed using the double-bundle Achilles allograft technique. Within the same surgery, a medial femoral incision was performed to reinsert the avulsion of the bone fragment rotated and distally retracted together with the MCL with bone anchors and Spike Washer. Two years after surgery, the patient enjoyed a 0/140-degree range of motion for flexion/extension. He had returned to sports and was pain-free. In conclusion, femoral avulsion of the MCL associated to PCL injury is a rare and nondescribed injury that, as opposed to most MCL isolated injuries, might benefit from early surgical reconstruction.
Keywords: knee ligament injuries; medial collateral ligament avulsion; posterior cruciate ligament tear; combined ligament injuries; surgical repair